2016
DOI: 10.1128/jvi.00335-16
|View full text |Cite
|
Sign up to set email alerts
|

Combined HIV-1 Envelope Systemic and Mucosal Immunization of Lactating Rhesus Monkeys Induces a Robust Immunoglobulin A Isotype B Cell Response in Breast Milk

Abstract: Maternal vaccination to induce anti-HIV immune factors in breast milk is a potential intervention to prevent postnatal HIV-1 mother-to-child transmission (MTCT). We previously demonstrated that immunization of lactating rhesus monkeys with a modified vaccinia More than 200,000 new pediatric human immunodeficiency virus (HIV) infections occur annually via mother-to-child transmission (MTCT), nearly half through breastfeeding (1). Antiretroviral (ARV) drugs can dramatically reduce the rate of MTCT, but in areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…A subsequent study by the same group showed that strong HIV Env-specific IgA responses could be induced in lactating macaques by vaccination (64). Our results provide evidence that protective mucosal IgA responses can also be induced by vaccination of the infant and thereby have the potential to provide long-term protection against viral acquisition compared to transient protection by maternal antibodies.…”
Section: Figsupporting
confidence: 50%
“…A subsequent study by the same group showed that strong HIV Env-specific IgA responses could be induced in lactating macaques by vaccination (64). Our results provide evidence that protective mucosal IgA responses can also be induced by vaccination of the infant and thereby have the potential to provide long-term protection against viral acquisition compared to transient protection by maternal antibodies.…”
Section: Figsupporting
confidence: 50%
“…BAMA was performed as described previously (54)(55)(56)(57)(58)(59). Briefly, HIV antigens were conjugated to polystyrene beads (Bio-Rad) and the binding of plasma IgG to the bead-conjugated HIV antigens was measured.…”
Section: Methodsmentioning
confidence: 99%
“…genotype for Fcγ receptor IIIa were used as the source of effector cells. CD4 + T cells were activated and infected with AE.CM235 as described (43), and binding to AE.CM235-infected target cells was determined by indirect surface immunofluorescence analysis as described (44).…”
Section: Methodsmentioning
confidence: 99%